PKP-010 Higher than recommended doses of colistimethate sodium in patients with multi-drug resistant gram-negative bacterial infections: a benefit or an increased risk of toxicity?. (24th March 2015) - Luque, S; Sorlí, L; Horcajada, J; Campillo, N; Alvarez-Lerma, F; Segura, C; Knobel, H; Montero, M; Garcia, R; Grau, S
Abstract : Background: Recent pharmacokinetic studies suggest the administration of higher colistimethate sodium (CMS) doses for treating multidrug resistant Gram-negative (MDR-GNB) infections. Purpose: The aim was to compare the efficacy, pharmacokinetics and toxicity of the manufacturer's recommended CMS doses (RD) versus higher doses (HD). Material and methods: Pharmacokinetic study performed at a university hospital in patients with MDR-GNB infections treated with CMS. Data: demographics, severity (APACHE-II), CMS dose, type of infection, colistin plasma concentration (Cminss before next CMS dose and at steady state), nephrotoxicity at day 7 (RIFLE criteria), clinical cure and crude mortality. CMS doses were selected by the clinicians' criteria. All patients treated with higher doses than those recommended by the national manufacturer were considered HD group. Cminss was measured by HPLC. Results: 102 included patients. Clinical and pharmacokinetic characteristics. Conclusion: More than 30% of patients received a higher than recommended CMS dose but they didn't achieve better clinical outcomes in terms of clinical cure and mortality and they developed nephrotoxicity more frequently, a fact probably related to the higher colistin plasma levels. These findings suggest the need to select which patient's profile can benefit from higher CMS doses. References and/or acknowledgements: None. No conflict of interest.